RECURRENCE OF THYROGLOSSAL DUCT CYST AFTER SISTRUNK OPERATION. - Manandhar, Sriti; Kandel, Dillu Ram; Panthi, Niranjan (Birat Journal of Health Sciences, 2020)
Introduction: Thyroglossal duct cyst (TGDC) is the most common form of congenital anomaly in the head and neck region with prevalence of 7%. Embryologically the thyroglossal duct tract gets atrophied by fifth to tenth week of gestation. If it does not atrophied it results in TGDC and operation is the treatment of choice. However, in spite of standard surgical treatment there is recurrence of cyst. Eight percent of thyroglossal duct cyst may reoccur after adequate surgical excision. Objectives: To identify the recurrence of thyroglossal duct cyst after standard sistrunk’s operation. Methodology: A retrospective chart review performed in all the patients who were diagnosed with thyroglossal duct cyst and were managed by Sistrunk operation in B.P Koirala Institute of Health sciences, department of ORL and Head and Neck surgery from 2013 January1to 2015 December 31.The study was conducted on 37 patients’ age ranging from 4years to 68years. All the patients who had undergone Sistrunk’s operation and histopathologically diagnosed with thyroglossal duct cyst were analysed through hospital records. All records were reviewed for age, sex, location of cyst in neck and with relation to hyoid bone, postoperative complication and recurrence. Results: There was male predominance 67.56% and female only 32.43%.The most of the patients were between 1-15 yrs age group (48.64%). Thirty two patients presented with infrahyoid thyroglossal cyst and five patients with suprahyoid thyroglossal cyst. The post operative complications were in the form of wound dehiscence, haematoma, seroma, infection and there were two cases with recurrence out of thirty seven patients after Sistrunk operation in the form of persistence discharging sinus. Conclusion: A Sistrunk’s operation is effective in treating primary thyroglossal duct cyst with a comparably low recurrence rate. The intraoperative rupture of cyst is the most important risk factors predicting postoperative recurrence of thyroglossal duct cyst. Meticulous dissection of the thyroglossal duct cyst is very essential for the better surgical outcome.